Some subregular germs for p-adic Sp4(F) - Kim Yangkon; So Kwangho (International Journal of Mathematics and Mathematical Sciences)
Shalika's unipotent regular germs were found by the authors in the case of G=Sp4(F). Next, subregular germs are also desirable, for at least f(1) is constructible in another form for any smooth function f by using Shalika germs. Some of them were not so hard as expected although to find all of them is still not done explicitly.